Universal Design Research as a New Materialist Practice - Hamraie, Aimi (Disability Studies Quarterly, 2012)
In Disability Studies, Universal Design (UD) is a concept that is often borrowed from an architectural or design context to mean an ideology of inclusion and flexibility with a range of applications in education, technology, and other milieus. This paper returns to UD as a design phenomenon, considering knowledge production practices as conditions of possibility for inclusive design. UD appropriates and redefines normalizing research methods, namely anthropometry, that were developed in the 19th century for uses that are contrary to disability rights and justice, such as eugenics, colonialism, and scientific racism. The paper argues that critical disability theory should understand work in UD research and design practice in order to formulate a nuanced, new materialist and historical disability epistemology, particularly in engagements with scientific knowledge. Keywords: Universal Design, accessibility, anthropometry, normate, misfit, 19th century science, eugenics, new materialism